Commercialized artemisinin derivatives combined with colistin protect against critical Gram-negative bacterial infection - Yonglin Zhou; Baichen Liu; Xiuling Chu; Jianqing Su; Lei Xu; Li Li; Xuming Deng; Dan Li; Qianghua Lv; Jianfeng Wang (Communications Biology, 2022)
The anti-malaria drugs artemisinin derivatives produce a synergistic antibacterial effect with colistin against Gram-negative bacteria by simultaneously inhibiting MCR-1 function and hindering flagella assembly and energy metabolism.